(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: The rapid advancement of technology has significantly transformed modern traffic management and road safety systems. Innovative technologies such as intelligent transportation systems (ITS), real-time traffic monitoring, automated traffic signals, and connected vehicle technologies have enhanced the efficiency and safety of road networks worldwide. These advancements help in reducing traffic congestion, minimizing accident rates, and improving emergency response times. Moreover, emerging technologies like autonomous vehicles and AI-based predictive analytics are reshaping the future of traffic management by enabling proactive safety measures and adaptive traffic control. This paper explores the various technological tools currently deployed in traffic management, their benefits, challenges in implementation, and the potential impact on reducing road accidents and enhancing overall traffic safety.